Efektivitas Model Pembelajaran PjBL Melalui Google Form terhadap Motivasi Belajar Siswa MTs - Muhammad Arifky Pratama; Irwandi Irwandi (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the effect of the PjBL learning model through Google Form on students' motivation at MTsN 1 Bengkulu Selatan. This research method uses a Non-Randomized Control-Group Pretest-Posttest Design. The results showed that the average value of learning motivation in the experimental class was 75.96, while in the control class is 47.87. The p-value obtained is 0.000. In conclusion, using the PjBL model through Google Form significantly influences student motivation than conventional learning. Keywords: Google Form, Learning Motivation, PjBL